TRANSFORMASI SOSIAL MELALUI PENDIDIKAN NONFORMAL: STUDI PUSTAKA TENTANG PRAKTIK PEMBERDAYAAN BERBASIS KOMUNITAS DI INDONESIA TIMUR - Junita Liliana Kundre; Alberthina Abetsi Haumahu; Ferdinanda. S. Noya; Rila (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Development disparities and limited access to formal education in Eastern Indonesia have led communities to adopt nonformal education as a key strategy for empowerment. This study aims to analyze how nonformal education practices drive social transformation in the region. Using a systematic literature review methodology, the research examined 32 scholarly sources published between 2010 and 2025 from databases including Google Scholar and Garuda. Thematic analysis focused on empowerment models, roles of local actors, social impacts, and implementation challenges. Findings reveal that nonformal education in Eastern Indonesia is deeply rooted in local wisdom, facilitated by customary leaders and religious figures, and fosters critical consciousness and collective action. Social transformation manifests through increased public participation, local economic strengthening, and evolving gender relations. However, program sustainability is hindered by short-term funding dependencies and weak integration with regional policies. The study underscores the need for institutional recognition of nonformal education as an equal pillar in human development.